Energy Management in Heat Treatment - Berg, Pontus (My University, 2014)
This master thesis report looks into the energy usage of a modern heat treating facility at the bearing manufacturer SKF in Gothenburg. In this report background studies on heat treatment, furnace technologies and energy aspects have been performed and compiled into a theoretical base. The main body of the work has revolved around the two approach methods, interviews with experts in the field energy and heat treatment and empirical data gathering, and the outcome of this approach method. The study has covered all the stages involved in heat treatment such as pre-washing, to post washing. The type of heat treatment that has been performed in this facility has mainly been bainitic hardening. In order to compare the results an overviewing study of another bainitic hardening facility on SKF was made. The outcome of the study was that the important factors to consider when improving energy efficiency on a heat treating facility is to first of all to establish what the current situation is, and use this as a base line. Areas which are important to address to optimize the energy performance of the facility is to make sure the burners are efficient, have low surface losses, keep the utilization of the facility high and recover as much as possible of the waste heat. The most suitable way to do this is to use the waste heat from the flue gases in the pre- or post-wash. For this particular facility it was found that the most energy effective measure would be to upgrade burner to regenerative models, lower the surface temperature with 20 K, pre heat ingoing atmospheric gases with the hot outgoing atmospheric gases and finally heat exchange the flue gases with the post wash. This will lead to energy savings of about 18 %.
Keywords: Energi; Hållbar utveckling; Kemiteknik; Energy; Sustainable Development; Chemical Engineering